Admissions Criteria as Predictors of CLS Student Success. - HUBBARD, JOEL DAVID; SAWYER, BARBARA G. (Clinical Laboratory Science)
A passing score on the American Society for Clinical Pathology Board of Certification (BOC) exam is a metric of a student's academic success in most Clinical Laboratory Science (CLS)/Medical Laboratory Science programs. It would be ideal if CLS/Medical Laboratory Science programs were able to predict a student's success when an individual applies for admission to a CLS/Medical Laboratory Science program. This study aimed to demonstrate that there was a positive correlation between admissions scores at the Texas Tech University Health Sciences Center (TTUHSC) School of Health Professions and students' performance on the BOC exam. Using simple linear regression analysis with Pearson correlation, specific criteria that are part of the application and admissions scoring process were used to determine the relationship. The results of the study indicated moderate positive correlation between certain criteria and BOC exam performance, but they provide enough information to make an admissions decision on students who would have the best chance of success in the TTUHSC CLS program and the profession.